Composition-structure–physical property relationship and nonlinear optical properties of multiferroic hexagonal ErMn1−xCrxO3 nanoparticles1. Issue 17 (27th February 2015) - Raneesh, B.; Nandakumar, K.; Saha, A.; Das, D.; Soumya, H.; Philip, J.; Sreekanth, P.; Philip, R.
<x xml:space="preserve">Abstract</x> Nanocrystalline multiferroic ErMn1−xCrxO3 exhibits canted antiferromagnetism with a spin-glass transition and strong nonlinear optical absorption.